Psychoanalytic Approach and Dreams Interpretation in Surah Yusuf - Al Areqih, Rashad (Indonesian Journal of Islamic Literature and Muslim Society, 2023)
This study examines specific concepts of the psychoanalytic approach related to dream interpretation and defense mechanisms within Surah Yusuf in the Holy Quran. These concepts are reevaluated from an Islamic perspective, based on the teachings of the Quran and the Sunnah of Prophet Muhammad. This article aims to discuss the psychoanalytic approach in Surah Yusuf from an Islamic viewpoint and how these concepts can be interpreted in the context of providing solace to Prophet Muhammad during challenging times. Specifically, this research investigates the tumultuous journey of Yusuf, his psychological suffering, and traumatic experiences, as well as how the Quran portrays dream interpretation and defense mechanisms in Surah Yusuf as an example of Prophet Muhammad in endurance and patience during his mission. The findings of this study contribute to a deeper understanding of psychoanalytic concepts, particularly dream interpretation and defense mechanisms, within the framework of a realistic and accurate Islamic perspective. The Islamic perspective demonstrates a strong balance between dreams and their interpretation tools, as well as between unconsciousness and defense mechanisms, ultimately fostering security, peace, and the ability to overcome traumatic experiences for individuals who hold firmly to faith and religious principles.